THE USE OF MIND MAP TO IMPROVE STUDENTS’ VOCABULARY AT SMP WARINGIN BANDUNG - Rasi Yugafiati; Tania Priscila (Eltin Journal : Journal of English Language Teaching in Indonesia, 2019)
The research concerns the problems found in teaching and learning English vocabulary. The students had difficulties in discovering the meaning of words and the application of the words. Vocabulary is the key in language skill. The aim of this research was to improve students’ vocabulary  mastery by applying mind map for  eight grade students at Waringin Junior High School in academic year 2018/2019. The method used in this analysis is Classroom Action Reseach (CAR) which consists of Planning, Acting, Observing, and Reflecting. This research was managed in two cycles. The participants of this reseach were eight grade students . The instruments used in this research were observation and test. From the data collected by the researcher, it can be drawn a conclusion that the use of mind mapping were able to improve students’ vocabulary mastery. It can be seen from the improvement of mean score of pre-test was 59,833. Then, the mean score of post-test1 increased 63,100, and mean score of post-test  2 was 80,733. Thus, it can be concluded that the mind map was the right method to be applied in teaching vocabulary.